Characteristic ground motions of the 25th April 2015 Nepal earthquake (Mw 7.9) and its implications for the structural design codes for the border areas of India to Nepal. (1st January 2017) - Sharma, Babita; Chingtham, Prasanta; Sharma, Varun; Kumar, Vikas; Mandal, H.S.; Mishra, O.P.
Highlights: Strong ground motion is dictated by the geo-morphological constraints and rupture directivity. The structural heterogeneity and non linearity have the strong role in attenuation of seismic waves. Nepal Earthquake was devastating in the border cities of India to Nepal. Extent of damage to the structures in India can be avoided if the existing building design code is followed. Abstract: The 25th April 2015 Nepal Earthquake was found associated with a series of aftershocks, and the mainshock rupture propagated predominantly towards SE direction where a major aftershock (Mw 7.3) rocked on 12th May 2015 to the east of the mainshock that enhanced the rate of occurrence of aftershocks in the affected region. We conducted a rigorous analysis of strong motion data to understand the characteristics of ground motion and their bearing on the structural design codes, responsible for the damage to the structures in the border area of India to Nepal. The effect of ground geology on the acceleration response spectra are also evaluated using main shock and its associated strong earthquakes. All the sites used in the present analysis are located on alluvium deposits showing a predominant period of 0.242 sec for horizontal components and at 0.193 sec for vertical components. Our results demonstrated that observed Peak Ground Acceleration (PGA) has prominent distribution in the border cities of UP and Bihar. PGA ranges from 3 to 80 cm/sec 2 in the study region for the epicentral distance varying from 120 km to 495 km with respect to the source zone (mainshock). The Peak Ground Velocity (PGV) varies from 1 to 16 cm/sec while the Peak Ground Displacement (PGD) lies in between 1 cm and 20 cm for the same area. Our study shows that variation of PGD, PGV, and PGA are controlled and dictated by the geo-morphological constraints, besides the nature and extent of structural heterogeneities of the sub-surface geological formation materials. The obtained normalised spectral amplifications are compared with the Bureau of Indian Standard code for construction of buildings which shows that the current Indian building design code is within the structural limits proposed for the seismic forces at all periods for alluvium sites, suggesting that the structural heterogeneity has the strong role contributing towards the intrinsic attenuation in the seismic wave propagating medium. Our analysis also shows a good correspondence with the nonlinearity of the seismic waves, which in turn controls the degree of damage in an area. We infer that extent of damage to the structures in the border cities of India, vicinity to the rupture zone can be avoided if the existing building design code could have been implemented as the earthquake risk resilient mitigation plan.